Kehujahan Sadd Ad-Dzari'ah Dalam Penundaan Kehamilan Pada Masa Pandemi Covid-19 - Fashihuddin Arafat (Universitas Kiai Abdullah Faqih (UNKAFA) Gresik, 2022)
The purpose of this study is to analyze the policy of delaying pregnancy during the Covid-19 pandemic as advised by the Head of the BKKBN or (National Population and Family Planning Agency) Dr. Hasto Wardoyo, Sp. OG (K). The Sadd Ad Dzariah method is used as an analytical knife with a descriptive-normative approach. The results of the study show that the policy of delaying pregnancy is permissible, meaning that it is permissible to use one of the hujjah or Istinbath of Islamic Law in certain cases which contain means or paths to benefit and not for means or paths to disobedience (mafsadatan), blasphemy Sadd Ad-Dzari' Ah is as a preventive effort, namely prioritizing a greater good interest than other interests and rejection of a bad thing that is bigger than other bad things. In other words, this appeal is an attempt to create benefit and an effort to prevent harm.